2007
DOI: 10.1111/j.1365-2133.2006.07717.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of IgA antibodies to desmogleins 1 and 3 in pemphigus vulgaris, pemphigus foliaceus and paraneoplastic pemphigus

Abstract: This study shows that in a considerable number of supposedly IgG-mediated pemphigus patients IgA to Dsg1 and Dsg3 is also present. In most cases the antigen specificity of the IgA follows the antigen specificity of the IgG, although in a small number of cases IgA is present against the Dsg not recognized by IgG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
3
42
0
2
Order By: Relevance
“…Similar to our patient, subcorneal pustular dermatoses without anti-Dsc1 IgA have been previously reported. 16,17 Clearly, as more sensitive detection methods become available, 9,18 the complexity of IGAP and pemphigus-related phenotypes in general is expected to further unfold. Further underscoring the complexity of IGAP, several cases have been reported with positive direct and indirect immunofluorescence evidence for IgA autoantibodies, but no reactivity to either Dsc or Dsg, [13][14][15] suggesting the existence of other, not yet identified, cell surface autoantigens in IGAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our patient, subcorneal pustular dermatoses without anti-Dsc1 IgA have been previously reported. 16,17 Clearly, as more sensitive detection methods become available, 9,18 the complexity of IGAP and pemphigus-related phenotypes in general is expected to further unfold. Further underscoring the complexity of IGAP, several cases have been reported with positive direct and indirect immunofluorescence evidence for IgA autoantibodies, but no reactivity to either Dsc or Dsg, [13][14][15] suggesting the existence of other, not yet identified, cell surface autoantigens in IGAP.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] A review of the literature indicates that SPD-like features can be associated with IgA antibodies targeting autoantigens other than Dsc1, whereas IgA reactivity against Dsc1 does not necessarily result in subcorneal pustule formation. Negative direct immunofluorescence can rarely be found in pemphigus vulgaris, but is certainly more common in IGAP, 17 presumably owing to the fact that IgA immune complexes are less stable and more sensitive to degradation. Conversely, IgA autoantibodies are far more common in apparently 'typical' IgG-mediated pemphigus vulgaris than generally assumed, as shown in two large studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mentink et al tested the sera of 100 cases of pemphigus patients (34 PF, 58 PV and 8 PNP) in both anti-Dsg-1 and 3 IgA ELISA tests and 54 sera were found to have IgA to one or both Dsgs. 131 They also found that more than half of the cases that showed IgA anti-Dsg in the ELISA presented negative staining for IgA in IIF and/or DIF. The ELISA thereby seems a more sensitive assay than IIF analysis for detecting anti-Dsg IgA antibodies.…”
Section: Definition and Epidemiologymentioning
confidence: 96%
“…60,63,72,114-131 Pruritus, pustules and annular lesions are present in almost half of the cases. Most of them do not show mucous lesions.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Circulating IgG 2 and IgG 4 subclass autoantibodies were also observed in 60% and 23.3%, respectively, of healthy relatives [101]. Additionally, some PV patients develop IgA and IgE classes of Dsg 3 antibodies [113,114]. …”
Section: Pemphigus Autoantibodiesmentioning
confidence: 99%